Uji Kualitas Kertas Seni Dari Pelepah Tanaman Salak MelaluiProses Biochemical Pulping Kultur Campuran JamurTrametes Versicolor Dan Pleurotus Ostreatus Dengan Menggunakan Lama Pemasakan Dalam Naoh - Saputri, Evi tyas, Dra. Aminah Asngad, M.Si (2016)
This study aims to determine quality art paper from the stem bark of plants through the process using a mixed culture biokraft Trametes versicolor and Pleurotus ostreatus in NaOH concentration of 15% with a variation of old ripening. This research was conducted at the Laboratory of Biology, Faculty of Teaching and Education University of Muhammadiyah Surakarta. The study design used was completely randomized design (CRD) with two factorial with 4 combinations and two replications. Factors used is long inoculation of white rot fungus Pleurotus ostreatus, Trametes versicolor and the old pulp cooking in 15% NaOH. The results showed that the treatment POTV 15% 1 Hour 45 Day has the highest tensile resistance with an average of 0:14 tensile resilience. Tensile resilience lowest is in treatment POTV 15% 1 Hour 30 Day is 12:08. Tear resistance test papers note that most high tear resistance in treatment POTV 15% 1 Hour 45 days with an average of 12.72 tear resistance and tear resistance is lowest POTV treatment 15% 2 Hours 30 days with an average of 4.88 torn. Test results showed that the sensory properties of the highest average value given panelist on paper texture art that 2,60 (coarse) is the treatment POTV 15% 1 Hour 45 Day, an assessment of the color is 2.6 (dark brown), namely the treatment POTV 15% 2 Hour 30 Day, vote on the appearance of 2.15 fibers (shown) is the treatment POTV 15% 1 Hour 45 Day and panelists votes against, namely 2.65 A (like) in the treatment POTV 15% 2 Hours 30 Days.